Comparative analysis of physiological and biochemical traits in tobacco leaves of varying quality during development - Yang, Yue; Chen, Ou; Guo, Weimin; Ma, Yunfei; Chen, Yi; Jiang, Yonglei; Shi, Nan; Zheng, Dongfang; Xi, Wanpeng; Hu, Binbin (Frontiers in Plant Science, 2025)
IntroductionDuring tobacco growth and development, variations in environmental conditions and cultivation practices can lead to the emergence of low-quality tobacco leaves (multi fertilizer and reviving tobacco leaves). Although most experiments have focused on the late roasting process of tobacco and related metabolites, few have reported the physiological and biochemical changes in the internal development stage of tobacco.MethodsComparative analyses of physiological, colorimetric, pigment, and routine chemical parameters across normal mature tobacco leaves and low-quality tobacco leaves revealed significant disparities in growth vigor, chromatic evolution, pigment accumulation, and primary metabolite profiles. At the same time, the ultrastructural changes of leaf cells were observed by electron microscope to reveal the dysfunction at the cellular level.ResultsThis study investigated physiological and biochemical differences between normal mature tobacco leaves and low-quality tobacco leaves during their growth stages. Results showed that normal mature tobacco leaves exhibited significantly lower a* values but higher L* and b* values compared to low-quality tobacco leaves. Additionally, the contents of β-carotene, lutein, and chlorophylls a/b in three tobacco types decreased through developmental stages. Normal mature tobacco leaves exhibited lower plastid pigments than low-quality tobacco leaves at all stages. The contents of starch, reducing sugar, and total sugar in normal mature tobacco leaves reached the highest levels of 45.98%, 25%, and 27.65%, respectively, which are generally higher than those in low-quality tobacco leaves. At the same time, the contents of protein, total phytoalkaloid, and total nitrogen in most parts of normal mature tobacco leaves were the lowest, reaching as low as 2.7%, 0.07%, and 0.97%. Chlorine and potassium levels were more balanced in normal mature tobacco leaves than in low-quality ones.DiscussionDifferent quality tobacco leaves show different growth characteristics and chemical composition changes in the development process. Future research should investigate cultivation practices (e.g., fertilization timing, topping protocols) to optimize leaf phenotype and quality, thereby informing sustainable tobacco production strategies.